2022
DOI: 10.1063/5.0072497
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-modulated spiking as a novel route to bursting: Coupling-induced mixed-mode oscillations by symmetry breaking

Abstract: Mixed-mode oscillations consisting of alternating small- and large-amplitude oscillations are increasingly well understood and are often caused by folded singularities, canard orbits, or singular Hopf bifurcations. We show that coupling between identical nonlinear oscillators can cause mixed-mode oscillations because of symmetry breaking. This behavior is illustrated for diffusively coupled FitzHugh–Nagumo oscillators with negative coupling constant, and we show that it is caused by a singular Hopf bifurcation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Here, we continue our study of two identical FHN units that are nonoscillatory when uncoupled and investigate the mechanism underlying the result that repulsive coupling can lead to mixed-mode oscillations [32]. We show that the coupled system possess a degenerate singularity in the singular limit → 0, and demonstrate -through a center manifold computation -that this singularity corresponds to a cusp.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Here, we continue our study of two identical FHN units that are nonoscillatory when uncoupled and investigate the mechanism underlying the result that repulsive coupling can lead to mixed-mode oscillations [32]. We show that the coupled system possess a degenerate singularity in the singular limit → 0, and demonstrate -through a center manifold computation -that this singularity corresponds to a cusp.…”
Section: Introductionmentioning
confidence: 69%
“…In our recent study of coupled bursting oscillators [32], we revisited the finding by Sherman [37] who showed that coupling of spiking cells can lead to bursting via slow desynchronization so that each burst is preceded by a large number of full action potentials (spikes). Before the transition to bursting, the averaged membrane potentials show SAOs reflecting amplitudemodulated spiking [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we explore transitions between quiescent states and collective oscillations in coupled networks of heterogeneous, excitable nodes. For the node dynamics, we treat two types of system, the first being the FitzHugh–Nagumo (FHN) model, which is a prototypical model of electrical excitability in biological cells ( Fitzhugh, 1961 ; Nagumo, 1962 ), is often used to investigate collective network dynamics, and has been used as a model for beta cells ( Scialla et al, 2021 ; Pedersen et al, 2022 ). For the second, we consider a conductance-based model of pancreatic beta cells designed to more closely reproduce the signalling dynamics in these cells ( Sherman et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bursting oscillation is a complex dynamical behavior consisting of comparatively big-amplitude waves and approximately simple harmonic micro-amplitude vibrations, and is universally studied with the help of the slow/fast decomposition analysis that is proposed by in Rinzel [17] in 1985. For example, Pedersen et al [18] identified a novel bursting form related to the pitchfork bifurcation of cycle attractors, which was caused by symmetry breaking. Patsios et al [19] introduced a complex mixed-mode oscillation triggered by the jump mechanism rather than the standard canard phenomenon.…”
Section: Introductionmentioning
confidence: 99%